2018
DOI: 10.15296/ijwhr.2019.25
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Education and Women Empowerment in Health: A Review of the Literature

Abstract: Objectives: Women constitute almost 50% of the world population and play a number of roles in the community. The present study aimed to assess the relationship between sex education and women empowerment in health. Methods: Based on the aim of the study, the data were obtained reviewing the related literature on electronic and non-electronic websites and using equivalent keywords published until the last week of February 2018. In addition, mesh terms and key words were included in this research. Inclusion crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Therefore, educating the spouses about the effect of behavioral risk factors on UTI is very important in planning strategies for preventing UTI during pregnancy. Furthermore, educating the spouses by health professionals with respect to their culture can increase their health knowledge about the sexual and genital hygiene and reduce the risk of urogenital infection among pregnant women (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, educating the spouses about the effect of behavioral risk factors on UTI is very important in planning strategies for preventing UTI during pregnancy. Furthermore, educating the spouses by health professionals with respect to their culture can increase their health knowledge about the sexual and genital hygiene and reduce the risk of urogenital infection among pregnant women (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Thammaraksa et al suggested that sexual education causes a significant increase in the attitude score of guidance school teachers (33). McGuirl and Wiederman as well as Mirzaii and Sharifi have also created a more positive attitude towards sexual issues by educating women and men (34,35). WHO emphasizes that planned programs regarding sexual issues positively influences on health sexual attitudes and behaviors (36).…”
Section: Discussionmentioning
confidence: 99%
“…This could be more evident when a study of female students was conducted. Female students who receive primarily abstinence knowledge has the least possibility on unplanned pregnancy [9]. However, the school-based sex education could provide various outcomes according to the knowledge taught to students.…”
Section: Sex Education and Policies In Western Countriesmentioning
confidence: 99%
“…However, the school-based sex education could provide various outcomes according to the knowledge taught to students. For instance, abstinence-plus programs were believed to bring the most positive outcomes of increasing protection and knowledge while reducing the risks [9]. This belief is derived from countless randomized trials with a large base number for scholars to draw a conclusion, which can be proved by results provided by students.…”
Section: Sex Education and Policies In Western Countriesmentioning
confidence: 99%
See 1 more Smart Citation